Preliminary in silico study of a novel paratransgenic weapon against malaria: Genetically modifying wild plasmodium populations via recombinant mosquito symbiont - Sun, Joshua; Candra, Daniel Christopher; Pramanda, Ihsan Tria; Bani, Mario Donald; Wu, Nicholas; Husada, William; Alexander, Jonathan; Saputra, Silvan; Aberly, Rachel Sofian; Fidelia, Michelle (International Journal of Basic and Applied Science, 2024)
Malaria is an infectious disease caused by Plasmodium spp., a protist whose infection is spread by Anopheles mosquito as a vector. A potential method to counter the infection is through paratransgenesis, a promising genetic control approach. This study proposed a new approach by using a transgene carried in a modified Ti plasmid hosted in Asaia bacterium to carry out two purposes: sensing the presence of Plasmodium protein biomarkers and transferring the toxin transgene to the parasite upon detection, thereby killing it without harming the Asaia carrier. The biosensor mechanism was created by repurposing a TonB dependent iron-uptake transport pathway to transcribe the vir genes of Agrobacterium tumefaciens that facilitate the gene transfer. The aim of this in silico project was to serve as a preliminary study on the likelihood of success of the aforementioned biosensor mechanism. This study utilized Alphafold and RCSB (Research Collaboratory for Structural Bioinformatic Protein Data Bank). As for the research tools: PyMOL, ClusPro website, and PRODIGY (PROtein binDIng enerGY prediction) server was used for data preparation, protein-protein docking and binding affinity analysis respectively. The results were assessed with t-test to analyze the significance of the binding affinity, in comparison to other studies that employed similar methods. The result showed Plasmodium protein GGCS (Gamma-glutamylcysteine synthetase) having the highest binding affinity with FecA (Fe(3+) dicitrate transport protein A). The preliminary data suggested that introducing the toxin transgene may be possible through vir gene transcription from the TonB pathway.